EFEITOS DO TREINAMENTO AERÓBIO SOBRE OS PARÂMETROS HEMODINÂMICOS, AUTONÔMICOS E INFLAMATÓRIO DE PACIENTES APÓS CIRURGIA DE REVASCULARIZAÇÃO DO MIOCÁRDIO. - ALMEIDA, Fabiano de Jesus Furtado (2019)
The aim of the present study was to investigate the effects of aerobic training on autonomic and hemodynamic parameters, and on plasma concentration of interleukin-6 (IL-6) of patients undergoing coronary artery bypass grafting (CABG). The study sample consisted of 13 patients undergoing successful CABG. Before and after 8 weeks, we evaluated autonomic and hemodynamic parameters (arterial pressure, heart rate and double product) [frequency indices; Low Frequency (BF), High Frequency (AF), AF / BF balance; indexes in the time domain; standard deviation of the RR interval (SDNN), square root mean square of the differences between adjacent normal RR intervals (rMSSS) (ms2), percentage of heart rate greater than 50 (ms2) (PNN50)] and an inflammatory parameter (IL- 6). Aerobic training was performed twice a week, with a 48-hr rest interval between each session for 8 weeks. There were no significant changes in systolic blood pressure (124.15 ± 9.92 vs. 121.77 ± 10.28 mmHg), diastolic blood pressure (79.31 ± 6.42 vs. 76.08 ± 6.18 mmHg) and double product (9060.31 ± 1467.55 vs. 8810.08 ± 1259.08 mmHg - bpm. However, for the LF indices [70.55 ± 10.27 vs. 58.82 ± 18.13 (nu)], HF [29.27 ± 10.30 vs. 41.07 ± 18.15 (nu)] and LF/HF (2.86 ± 1.46 vs. 2.01 ± 1.54) there were significant differences. Additionally, after 8 weeks of aerobic training a significant reduction in the concentration of IL-6 (644.60 ± 475.12 vs. 403.97 ± 226.50 pg/ml) was observed. The practice of aerobic training improved autonomic parameters, as well as reduced inflammation in patients undergoing CABG.